Safety and efficacy of a feed additive consisting of a zinc(II)–betaine complex for all animal species (Biochem Zusatzstoffe Handels‐ und Produktionsges. mbH). (21st February 2023) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; Puente, Secundino López; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a zinc(II)–betaine complex as nutritional additive for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive is safe for chickens for fattening. This conclusion could be extrapolated to all animal species and categories provided that the maximum authorised levels in the EU for total zinc in feed are not exceeded. The FEEDAP Panel concluded that the use of the zinc(II)–betaine complex in animal nutrition is of no concern for consumer safety provided that the maximum authorised total zinc levels in feed are respected. The additive is considered to be a skin and respiratory sensitiser due to the presence of nickel; it is irritant to the eyes, but not to the skin. The use of the additive in animal nutrition for terrestrial animals and land‐based aquaculture at the proposed use levels is considered safe for terrestrial and aquatic ecosystems. The available data do not allow the conclusion to be made on the safety of the additive for the marine sediment when it is used in sea cages. Based on the deposition of zinc in edible tissues/organs in chickens for fattening, the FEEDAP Panel concluded that the additive is a source of bioavailable zinc, comparable to the standard inorganic zinc source, and therefore, the additive is efficacious in meeting the birds zinc requirements. This conclusion can be extrapolated to all animal species and categories.